1972
DOI: 10.1111/j.1365-2141.1972.tb03492.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe Allergic Pulmonary Oedema after Plasma Transfusion

Abstract: Summary. Three patients with haemophilia suffered severe febrile reactions after transfusions of fresh frozen plasma and developed pulmonary oedema which did not appear to be due to circulatory overload. The chest radiographs were characterized by widespread patchy rounded opacities resembling bronchopneumonia. In one of the patients the reaction proved fatal; in the other two, treatment was followed by the rapid resolution of symptoms, clinical signs and the abnormal chest radiograph. In two of the patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 11 publications
2
35
0
1
Order By: Relevance
“…Histological findings in patients who died from TRALI are consistent with early acute respiratory distress syndrome (ARDS), showing interstitial and intra-alveolar oedema (Felbo & Jensen, 1962;Flury & Reutter, 1966;Kernoff et al, 1972;Wolf & Canale, 1976;Popovsky & Moore, 1985;Silliman et al, 1997;Dry et al, 1999) and an extravasation of neutrophils into the interstitial and air spaces (Kernoff et al, 1972;Wolf & Canale, 1976;Silliman et al, 1997;Dry et al, 1999). In addition, hyaline membranes and destruction of the pulmonary architecture have been reported (Wolf & Canale, 1976;Silliman et al, 1997).…”
Section: Pathological Findings In Trali Patientsmentioning
confidence: 80%
“…Histological findings in patients who died from TRALI are consistent with early acute respiratory distress syndrome (ARDS), showing interstitial and intra-alveolar oedema (Felbo & Jensen, 1962;Flury & Reutter, 1966;Kernoff et al, 1972;Wolf & Canale, 1976;Popovsky & Moore, 1985;Silliman et al, 1997;Dry et al, 1999) and an extravasation of neutrophils into the interstitial and air spaces (Kernoff et al, 1972;Wolf & Canale, 1976;Silliman et al, 1997;Dry et al, 1999). In addition, hyaline membranes and destruction of the pulmonary architecture have been reported (Wolf & Canale, 1976;Silliman et al, 1997).…”
Section: Pathological Findings In Trali Patientsmentioning
confidence: 80%
“…Although several studies suggested that transfusion-induced dysregulation of neutrophils may in part be responsible for the development of TRALI, 1,45,46 only recently have several of the mechanisms responsible for these alterations been elucidated. Given the clinical correlations implicating antibodies in the development of TRALI, 17,23 early studies examined the potential involvement of antibody-mediated perturbation of normal neutrophil function.…”
Section: Benchmentioning
confidence: 99%
“…We do not believe the same explanation can be applied to our observations of widespread degranulation of granulocytes, membrane-bound cytoplasmic fragments between the granulocytes and endothelium, and the focal finding of granulocytes directly contacting denuded capillary walls. These Kernoff et al 6 Eastlund et al 9 Silliman et al 21 …”
Section: Time Of Transfusionmentioning
confidence: 99%
“…Wolf and Canale 7 described a 13-year-old girl with thalassemia who died of transfusionrelated acute lun<* injury within 12 1 / hours of transfusion. Autopsy showed congested lungs (800 g total) with dilated subpleural lymphatics and abundant edema fluid Marked accumulation of intra-alveolar inflammatory cells was noted as were hyaline membranes and congested alveolar capillaries Kernoff et al 6 described a case of a 9-year-old patient with hemophilia who died 13 hours after transfusion; the lungs were grossly edematous with basal atelectasis Extensive hemorrhagic edema and areas of agonal acute pneumonitis characterized by alveolar polymorphonuclear exudate and fibrin deposition were present Eastlunri et al Most autopsy cases have demonstrated histologic evidence of moderate to severe pulmonary edema, as well as alveolar changes that are most commonly associated with infection and ARDS. Few have revealed pulmonary intravascular leukoagglutination, the presumed mechanism of transfusion-related acute lung injury hypothesized from animal and clinical studies.…”
Section: Time Of Transfusionmentioning
confidence: 99%